INVESTIGATING HOLLOW FOAMED CONCRETE BLOCK WALLS: EFFECT OF USING ADDITIVES AND JOINT MATERIAL TYPE - Abubaker Mohammed Sulaiman; Ameer A. Hilal; Zaid Al-Azzawi (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
This study is concerned with the effect of the use of additives and joint material type (cement mortar and adhesive material) in hollow foamed concrete blocks through testing walls built with these blocks by applying axial compression force. In this study, three walls were built. In the first wall, cement mortar as a joint material between the cuboid blocks was used. While, in the second wall bonding adhesive material was used. In the third wall, conventional of foamed concrete (without additives) was used in producing the hollow block units which were bonded by using a bonding adhesive material. The compressive behavior and modulus of elasticity were studied, and the deformation and failure of masonry walls were studied as well. It was observed that the use of a bonding adhesive to bond the block units made of additives gave the highest compressive strength (1.08 MPa) which was about (27 and 38) % higher than the cement mortar wall and the hollow concrete block wall without additives respectively and the modulus of elasticity (46.9 MPa) and also gave the highest bearing capacity (214 kN). However, the use of a bonding adhesive helped in reducing the wall displacement. Finally, it was found that the lower the fractal dimension (D) the stronger the wall.